If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42b + 7 = 0 Reorder the terms: 7 + 42b = 0 Solving 7 + 42b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 42b = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 42b = 0 + -7 42b = 0 + -7 Combine like terms: 0 + -7 = -7 42b = -7 Divide each side by '42'. b = -0.1666666667 Simplifying b = -0.1666666667
| -3(2t+9)=-15 | | 3x-3+x=57 | | r^3-5r^2+7r-35=0 | | 8t^4+40t^3+t+5=equation | | 8x=x^2-1 | | 24c+18= | | N/37=14 | | 3(f-9)=27 | | Ln(2x-2)=ln(1-2x) | | f(6)=4x+x^2 | | 3x4^2/12 | | 2c+7=-3c | | 7x-19=3x+4 | | 3(X-7)-4(y+9)=40 | | 10(x-5)=-116 | | 8+8y=2x | | 8x-4y=p | | 3x+2+x=50 | | 2.0*2.8= | | 8x+4y=p | | u+1.33=4.59 | | X(-2x+7)=3 | | 4=8+3(2t-1) | | v-1.93=5.9 | | 5(x+11)=110 | | 50+15m=20+25m | | 4(x-5)-5(y+8)=80 | | x+3x+2=50 | | 11k-2=15k+1 | | y+16=26 | | -8(x-8)=4(x-4) | | 14y=238 |